Return migration from the United States to Mexico in a moment of economic and political crisis - Montoya-Ortiz, Merari Stephanie; Granados-Alcantar, José Aurelio; Jauregui-Díaz, José Alfredo (Papeles de Población, 2018)
This paper examines the recent migration of return from the United States to Mexico during the period 2004 to 2014, a temporary cohort where proliferation of anti-immigrant state laws in the United States of America, such as the Sensenbrenner Act approved in December 2005 (Borderprotection , Antiterrorism and Illegal Immigration Control Act) and the Arizona SB 1070 Act passed in 2009, both aimed especially at Mexicans, resulting in an unprecedented increase in expulsions from within the United States. Likewise, the US economic crisis that began in 2007 and reached its peak in 2008 resulted in an increase in return to Mexico, that for 2004-2009 report 460 thousand migrants that come back to Mexico form USA and the most recent migratory and humanitarian crisis in 2014 of unaccompanied migrant minors, which achieved 61 thousand cases.